Intravenous lidocaine decreased oxygen-desaturation episodes induced by propofol-based sedation for gastrointestinal endoscopy procedures: a prospective, randomized, controlled trial - Xiu-Ru Qi; Yu-Xuan Qi; Ke Zhang; Wen-Wen Hao; Li-Xin An (BMC Anesthesiology)
Abstract Background As a popularly used analgesic adjuvant, intravenous (IV) lidocaine could reduce the consumption of propofol in painless gastrointestinal (GI) endoscopy. However, whether IV lidocaine could affect the incidence of oxygen-desaturation episodes (ODE) during painless GI endoscopy is still unknown. Therefore, we tested the hypothesis that IV lidocaine could decrease the incidence of propofol-induced ODE and involuntary movements in patients during GI endoscopy. Methods Three hundred twenty-two patients scheduled for GI endoscopy were randomly divided into lidocaine group and control group. After midazolam and sufentanil injection, a bolus of 1.5 mg/kg lidocaine was given and followed by continuous infusion of 4 mg/kg/h in lidocaine group, whereas the same volumes of saline solution in control group. Then, propofol was titrated to produce unconsciousness. The primary outcome was the incidence of ODE during the procedure. The secondary outcomes were the incidence of different degree of hypoxia and corresponding treatments and the involuntary body movements. Results A total of 300 patients were finally included in the analysis, 147 patients in lidocaine group and 153 in control group. The incidence of ODE was 22% in lidocaine group and 39% in control group (OR:0.052; 95%CI: 0.284–0.889; P = 0.018). IV lidocaine also improved the occurrence of different degree of hypoxia (P = 0.017) and needed few treatments (P = 0.028). The incidence of involuntary body movements (14% vs 26%, P = 0.013) and adverse circulatory events was decreased by IV lidocaine. Conclusions IV lidocaine adjuvant to propofol-based sedation could reduce the incidence of oxygen-desaturation episodes and involuntary body movements, with fewer adverse circulatory events. Trial registration Chinese Clinical Trial Registry ChiCTR2100053818. Registered on 30 November 2021.